2015
DOI: 10.1016/j.ijplas.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Strain-path change induced transients in flow stress, work hardening and r-values in aluminum

Abstract: Commercially pure aluminum with random texture was prestrained either by rolling or by uniaxial compression, and then tested in uniaxial tension to study the transients in flow stress, work hardening and r-value induced by the strain-path change. New experimental results are reported on the variation of the r-value and the permanently reduced work hardening subsequent to the strain-path change. A continuum plasticity model was developed that can reproduce the observed behavior. The model applies a second-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 97 publications
2
52
0
Order By: Relevance
“…The HAH model (Barlat et al, 2014) is modified to capture SPC transients observed in aluminum, i.e., hardening stagnation after reverse SPCs and permanent softening after orthogonal SPCs. Predictions by the HAH model are compared to the MHH model (Mánik et al, 2015), which was originally developed for aluminum. The MHH model turned out to be directly applicable to an extra deep drawing quality (EDDQ) steel without any modifications.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HAH model (Barlat et al, 2014) is modified to capture SPC transients observed in aluminum, i.e., hardening stagnation after reverse SPCs and permanent softening after orthogonal SPCs. Predictions by the HAH model are compared to the MHH model (Mánik et al, 2015), which was originally developed for aluminum. The MHH model turned out to be directly applicable to an extra deep drawing quality (EDDQ) steel without any modifications.…”
Section: Introductionmentioning
confidence: 99%
“…These anisotropic hardening behaviors can, in general, be described by a yield surface that changes shape and size during plastic deformation. A recent review can be found in Mánik et al (2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations